HERMENEUTIKA M. ËÄBED AL-JÄBIRÄª DAN IMPLIKASINYA TERHADAP HUKUM ISLAM (Kasus Nasakh dan Nikah MutËah) - Yahya, Mohamad (AS-SALAM, 2012)
Al-JÄbirÄ«âs hermeneutics and its implications for Islamic law is topic of thisarticle. Framework thinking of al-JÄbirÄ«âs hermeneutics was constructed onthe basis of two principles, al-faá¹£l and al-waá¹£l. Al-faá¹£l principle was appliedby using three approaches; structural analysis, historical criticism, andideological criticism, while the principle of al-waá¹£l using mathematicalintuitionapproach. He had applied that methodological construction in theinterpretation of the Qurâan, as the source of all sources of Islamic law. Theimplication is reconstruction, and even deconstruction, of various theoriesand themes of Islamic law. Theoretically, one of which is about nasakh. Forhim, no nasakh in the Qurâan, except humanâs understanding about lawis changed. While thematically, one of which is mutËah. As a consequenceof the absence nasakh in the Qurâan, for him mutËah remain in force if thecondition and the situation requires.Keywords: Al-JÄôbirÄ«ô, hermeneutika, nasakh, dan mutËah.